Comprehensive Investigation of Structural, Electronic and Optical Properties of KBaP Using Density Functional Theory - AMINE, Aidouni Ahmed; MOUNIR, Ould - Mohamed; ABDELKADER, Aissat; Souheil, Belbachir (The Eurasia Proceedings of Science Technology Engineering and Mathematics, 2024)
In this study, we investigate the structural, mechanical, dynamical, electronic, thermodynamic, and optical properties of KBaP using density functional theory (DFT) within the plane-wave pseudopotential method as implemented in Quantum ESPRESSO. Our structural analysis reveals that the β-phase of the halfHeusler structure is the most stable, with an equilibrium lattice parameter of 7.36 Å. Mechanical and dynamical stability are confirmed through the calculation of elastic constants and phonon dispersion, respectively. Electronic properties show that KBaP is a direct bandgap semiconductor with a bandgap of 1.30 eV at the X-X point, suggesting potential applications in optoelectronic devices. Additionally, we explore the thermodynamic and optical properties, further demonstrating the potential of KBaP in energy-related applications. Our findings provide a comprehensive understanding of KBaP, establishing it as a promising material for future technological developments.